1988
DOI: 10.1039/p19880001599
|View full text |Cite
|
Sign up to set email alerts
|

The 4α-demethylation of lanostenone

Abstract: Cyclopalladiation of lanostenone oxime occurs at the equatorial 4x-methyl group. Oxidation of the acetate of this complex w i t h Pb(OAc), forms the 4a-acetoxymethyl compound which on reduction and hydrolysis yields 4P-demethyl-lanostenone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…The saturated analogues 1-p-menthen-9-yl 2-methyl butanoate 9 and 1-p-menthen-9-yl 3-methyl butanoate 10 were prepared by esterification of both (+)-(4R)-1-p-menthen-9-ol (1R)-8 and (-)-(4S)-1-p-menthen-9-ol (1S)-8. These were prepared by selective hydroboration/oxidation with disiamylborane on the exocyclic C=C bond of (R)-or (S)-limonene, as described by Carr et al [14] According to the literature, 2 has been reported in Artemisia absinthium [15] and 5 has been reported in the kumquat Fortunella japonica Swingle. [16] 1,8(10)-p-menthadien-9-yl 2-methylbutanoate 6, 1,8(10)-p-menthadien-9-yl 3-methylbutanoate 7, 1-p-menthen-9-yl 2-methylbutanoate 9 and 1-p-menthen-9-yl 3-methyl butanoate 10 are reported here for the first time in a natural product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The saturated analogues 1-p-menthen-9-yl 2-methyl butanoate 9 and 1-p-menthen-9-yl 3-methyl butanoate 10 were prepared by esterification of both (+)-(4R)-1-p-menthen-9-ol (1R)-8 and (-)-(4S)-1-p-menthen-9-ol (1S)-8. These were prepared by selective hydroboration/oxidation with disiamylborane on the exocyclic C=C bond of (R)-or (S)-limonene, as described by Carr et al [14] According to the literature, 2 has been reported in Artemisia absinthium [15] and 5 has been reported in the kumquat Fortunella japonica Swingle. [16] 1,8(10)-p-menthadien-9-yl 2-methylbutanoate 6, 1,8(10)-p-menthadien-9-yl 3-methylbutanoate 7, 1-p-menthen-9-yl 2-methylbutanoate 9 and 1-p-menthen-9-yl 3-methyl butanoate 10 are reported here for the first time in a natural product.…”
Section: Resultsmentioning
confidence: 99%
“…Yield 83%, purity 98%, ee 98%. MS: m/z 134 (39), 119 (86), 106 (100), 105 (38), 94 (19), 93 (32), 92 (38), 91 (51), 84 (8), 79 (39), 77 (18), 68 (23), 67 (24), 57 (49), 41(14). 1 H-NMR: 1.16 (t, J = 7.5 Hz, 3H); 1.45-1.55 (m, 1H); 1.65 (br s, 3H); 1.83-2.24 (m, total 6H); 2.37 (q, J = 7.5 Hz, 2H); 4.59 (br s, 2H); 4.97 (br s, 1H); 5.05 (dd, J = 1.1 Hz, 1H); 5.38-5.42 (m, 1H) 13.…”
mentioning
confidence: 99%
“…The present paper also presents evidence of a new kind in support of 'free' nitric oxide as an intermediate. Some of the findings have been summarised in a short preliminary report [18].…”
mentioning
confidence: 99%
“…Transition metal catalysts are especially useful for synthesis of some steroids from triterpenoids. Mechanism of chemical hydroxylation of a triterpenoid E -lupanone oxime with palladium catalyst is a good example of this type of C–H bond activation and oxidation (Carr et al 1988 ). E -Lupanone oxime consists of C=N–OH group which is directing sodium chloropalladate to complex with adjacent methyl group.…”
Section: Stereoselective Hydroxylationmentioning
confidence: 99%